Improving Students’ Learning Interest Using Cooperative Learning: The TGT Model in Fourth Grade IPAS - Sani, Nurul Kami; S. Pontoh, Aprilia Monica; Zulnuraini, Zulnuraini; Nashrullah, Nashrullah (FKIP - Universitas Riau, 2025)
This study aims to enhance elementary students’ learning interest in Science and Social Studies (IPAS) through the application of the cooperative learning model, Teams Games Tournament (TGT). The research was conducted as Classroom Action Research (CAR) involving two cycles, each consisting of two meetings. Data were collected using a yes/no learning interest questionnaire and observation sheets measuring both teacher and student activity. The TGT model was implemented through five main stages: class presentation, team study, games, tournaments, and rewards. The results demonstrated a substantial increase in the implementation quality of teaching activities, with teacher activity scores improving from 85.3% in Cycle I to 97.1% in Cycle II, and student activity scores from 82% to 97%. Furthermore, students’ average learning interest rose from 50.8% in the first cycle to 83% in the second. Improvements were also observed across all interest indicators, including attention, enjoyment, curiosity, and participation. These findings indicate that the TGT model effectively supports a student-centered, interactive, and engaging learning environment, fostering emotional involvement and active participation. Therefore, the TGT model is recommended as a promising instructional strategy for increasing learning interest in primary education settings.